2018
DOI: 10.1021/acs.inorgchem.8b00537
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure of Manganese Corroles Revisited: X-ray Structures, Optical and X-ray Absorption Spectroscopies, and Electrochemistry as Probes of Ligand Noninnocence

Abstract: Presented herein is a detailed multitechnique investigation of ligand noninnocence in S = / manganese corrole derivatives at the formal Mn oxidation state. The Soret maxima of Mn[T pXPC]Cl (T pXPC = meso-tris( p-X-phenyl)corrole, where X = CF, H, Me, and OMe) were found to red-shift over a range of 37 nm with increasing electron-donating character of X. For Mn[T pXPC]Ph, in contrast, the complex Soret envelopes were found to be largely independent of X. These observations suggested a noninnocent corrole-like l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 65 publications
10
46
0
Order By: Relevance
“…Recently, Nocera and Kar independently reported that several copper complexes of meso ‐aryl‐substituted corroles consist of the central copper(II) ion and the divalent corrole π‐radical ligand with strong antiferromagnetic interaction between the copper(II) and the π‐radical fragment, thereby behaving as an overall singlet spin‐state even at room temperature. Similar ligand non‐innocent behaviors have also been known for silver octabromocorroles, chloroiron and nitrosoiron corroles, triphenylphosphine cobalt corroles, and chloromanganese corroles . Another important observation is the metal‐ligand interaction depending on the size of the ligand.…”
Section: Introductionsupporting
confidence: 58%
“…Recently, Nocera and Kar independently reported that several copper complexes of meso ‐aryl‐substituted corroles consist of the central copper(II) ion and the divalent corrole π‐radical ligand with strong antiferromagnetic interaction between the copper(II) and the π‐radical fragment, thereby behaving as an overall singlet spin‐state even at room temperature. Similar ligand non‐innocent behaviors have also been known for silver octabromocorroles, chloroiron and nitrosoiron corroles, triphenylphosphine cobalt corroles, and chloromanganese corroles . Another important observation is the metal‐ligand interaction depending on the size of the ligand.…”
Section: Introductionsupporting
confidence: 58%
“…The Mo(4d z 2)-corrole("a 2u ") interaction evident in the HOMO−2 and LUMO (Fig. 5) is, topologically, exceedingly similar to analogous interactions involving the 3d z 2 orbital in MnCl, 23 FeCl, [10][11][12][13][14][15] FeNO, 27 and Co-PPh 3 31 corroles. Importantly, this picture was fully borne out by an examination of the 4d-based natural bond orbitals (NBOs) of the molecule.…”
Section: Dalton Transactions Papermentioning
confidence: 70%
“…To gain an estimate of the strength of the Mo(4d z 2)corrole •2− antiferromagnetic coupling, we optimized the corresponding ferromagnetically-coupled (S = 3/2) state of Mo[TPC]O and found its energy to be ∼0.9 eV above the ground state (for the B3LYP functional). In stark contrast, the ferromagnetically coupled states of MnCl, 23 FeCl, [10][11][12][13][14][15] FeNO, 27 and Co-PPh 3 31 corroles were invariably found to occur only a few tenths of an eV higher in energy relative to the antiferromagnetically-coupled ground state, a testament to much stronger metal-ligand orbital interactions for the heavier transition elements. This result provides a rare Paper Dalton Transactions measure of metal-ligand magnetic coupling for a 4d transition metal.…”
Section: Dalton Transactions Papermentioning
confidence: 96%
See 1 more Smart Citation
“…The sterically hindered TMP ligands was chosen to improve the stability of the Cr(IV) complex, but the differences in peripheral transition metal d electron counts, XAS has only been infrequently applied to Cr porphyrins and indeed to metalloporphyrin-type complexes in general, except for those involving Mn and Fe. [1][2][3][4][5][6][7][8] Indeed, only one directly relevant study has been reported in the literature, focusing on Cr IV [TTP]O and Cr V [TTP]N, where TTP 2À is the dianion of meso-tetra(p-tolyl) porphyrin. 9 Understandably, we have used substantially improved theoretical methods in the present study to model the Cr K-edge XAS data on the high-valent compounds 2 and 3, and where appropriate, we will point out similarities and differences relative to the earlier study.…”
Section: Introductionmentioning
confidence: 99%